Physicochemical and microbial quality of cow and buffalo raw milk collected from different organized dairy farms of Varanasi, India - Lal, Dwarki; Rai, Dinesh Chandra; ., Arvind; Bhateshwar, Vinod; Muwal, Hitesh (Indian Journal of Dairy Science, 2021)
The current study was carried out to estimate the physicochemical properties, microbial quality, and adulteration pattern of cow and buffalo raw milk collected from different organized dairy farms in Varanasi, India. Raw milk samples were analyzed and found that the cow’s raw milk constituents i.e. the per cent of lactose (4.31) was significantly (P<0.05) different whereas fat (3.76), protein (3.37) solid not-fat (8.51), and specific gravity (1.028) were observed non-significant among collected samples. However, the percent of fat (6.63), protein (4.17), and specific gravity (1.029) were recorded significantly (P<0.05) different but the average percentage of lactose (4.81) and solid not-fat (8.95) was noted non-significantly different in the raw milk of buffalo. All raw milk samples were of good quality grades as determined by the MBRT test. The microbial count confirmed the presence of significantly (P<0.05) low microbial load in all cow (3.53 log CFU/ml) as well as in buffalo raw milk (3.46 log CFU/ml) samples. In adulterations analysis; all raw milk samples were free from water, starch, cane sugar, and glucose. Besides different hazardous chemical adulterants, all raw milk samples were free from urea, hydrogen peroxide, ammonium, and nitrates.